Discrepancy between financial disclosures of authors of clinical practice guidelines and reports by industry. Issue 2 (January 2017) - Andreatos, Nikolaos; Zacharioudakis, Ioannis M.; Zervou, Fainareti N.; Muhammed, Maged; Mylonakis, Eleftherios
Abstract : Abstract: There is a substantial effort to increase the accuracy of conflicts of interest (COI) reporting, and reduce the influence of COI between physicians and industry, especially as it relates to clinical practice guidelines. We used the newly implemented Open Payments dataset to evaluate the accuracy of COI disclosures of authors of clinical practice guidelines that were either newly published or revised within 2014 and were included in the National Guideline Clearinghouse (NGC) website (maintained by the U.S. Department of Health and Human Services). Authors were considered as having inaccurate COI disclosure if they had not reported all companies from which they had received funds >$5000 in the 12 months preceding the guideline's publication. We identified 223 guidelines that were either newly published (109/223; 48.9%) or revised (114/223; 51.1%) within 2014 and were included in the NGC website. Among the 1329 guideline authors with available Open Payments data, 523 received >$5000 from at least 1 healthcare-associated entity. However, only 56 out of the 523 authors (10.7%) were found to have accurate COI disclosure. The percentage of authors with accurate COI disclosure in revised guidelines was significantly lower than in newly published guidelines (6.8% vs 14.3%; P  < 0.01) and was also found to differ between specialties. Furthermore, authors were less likely to inaccurately disclose "research payments" (37/49, 75.5%) compared to "general payments" (488/559, 87.3%, P  = 0.02) as well as "other/associated research funding" (430/506, 85.0%, P  = 0.08). No statistically significant association was detected between funding amount and disclosure accuracy. The majority of guideline authors lacked significant COIs, but among authors that received significant funds from at least 1 healthcare-associated entity the frequency of accurate disclosure was low. These findings indicate that the current process of disclosing COIs may be suboptimal and a proactive approach should be adopted in order to minimize COI reporting discrepancies. Furthermore, every effort should be undertaken to ensure the completeness and accuracy of the data recorded in the Open Payments database. Abstract : Supplemental Digital Content is available in the text